PENGARUH EDUKASI PENCEGAHAN ANEMIA TERHADAP PENGETAHUAN REMAJA PUTRI MENGGUNAKAN MEDIA VIDEO ANIMASI (Politeknik Kesehatan Kemenkes Bandung, 2023)
Background: Adolescent girls are more susceptible to anemia due to monthly menstrual cycles, lack of the knowledge, and lack of effective media to increase knowledge about anemia prevention. Therefore, it is necessary to provide anemia prevention education to young women by using the right animated video media according to the characteristics of the target. Objective: To determine the effect of anemia prevention education on knowledge of adolescent girls using animated video media at SMPN 1 Ciparay. Methods: This study used a pre-experimental design with one group pretest-posttest without control design, with a total of 74 students from a total population of 281 students. Data analysis used the Wilcoxon test to prove the research hypothesis. Results: The average score of students' knowledge before being given education using animated video media was 66.52. The average score of student knowledge after being given education using animated video media is 91.16. The percentage increase in knowledge is 24.64%. Wilcoxon test analysis, the results obtained p = <0.001 which means there is a significant change. Conclusion: There is an effect of anemia prevention education on the knowledge of adolescent girls using animated video media at SMPN 1 Ciparay.